2009
DOI: 10.3171/2008.10.jns08978
|View full text |Cite
|
Sign up to set email alerts
|

Use of the h index in neurosurgery

Abstract: The h index appears to be a robust statistic for comparing academic output of neurosurgeons. Within the field of academic neurosurgery, clear differences of h indices between academic ranks exist. On average, an increase of the h index by 5 appears to correspond to the next highest academic rank, with the exception of chairperson. The h index can be used as a tool, along with other evaluations, to evaluate an individual's productivity in the academic advancement process within the field of neurosurgery but sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
240
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(246 citation statements)
references
References 18 publications
6
240
0
Order By: Relevance
“…Nonetheless, at least one previous study examining h-indices found a strong correlation between the h-index calculation results of Scopus and Google Scholar, another widely used h-index calculator, making it unlikely that database choice provided inaccurate conclusions. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, at least one previous study examining h-indices found a strong correlation between the h-index calculation results of Scopus and Google Scholar, another widely used h-index calculator, making it unlikely that database choice provided inaccurate conclusions. 14 …”
Section: Discussionmentioning
confidence: 99%
“…14 An h-index analysis comparing very different scientific disciplines, such as theoretical physics and medicine, would have unclear relevance given the different types of research conducted. However, examination and comparison of fields within medicine, more specifically surgical fields, provides potentially valuable insight into the degree to which research is emphasized as well as other possible factors influencing scholarly productivity within a specific field.…”
Section: Introductionmentioning
confidence: 99%
“…None of these studies included a nonanesthesiologist control group, but similar analyses of radiation oncologists and faculty in neurosurgery and urology suggest anesthesiologists publish less often than do these other specialists. [7][8][9] Cardiothoracic anesthesia may be an exception; faculty members from 30 randomly selected cardiothoracic anesthesia fellowship programs contributed 28 ± 46 publications on average, with senior faculty having more than junior faculty and ACGME-accredited fellowship program faculty having more than those in nonaccredited programs. 2 Still, the 15 faculty directing non-ACGME cardiothoracic anesthesia fellowships had 20 ± 24 publications, 2 which is several fold more than the directors of ACGME-accredited core anesthesia residency programs included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These bibliometric indices-the h-index in particular-have been widely applied to neurosurgery [17][18][19][20][21][22][23][24][25]. Using this database, we identified the 25 top-ranked North American pediatric neurosurgeons based on the manually calculated h-index from Scopus (Elsevier, www.scopus.com) [17].…”
Section: Introductionmentioning
confidence: 99%